2009
DOI: 10.1088/1741-2560/6/3/035010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient suitability for a retinal prosthesis using structural and functional tests of inner retinal integrity

Abstract: The purpose of this study was to assess inner retinal structure and function in patients with retinitis pigmentosa (RP) using optical coherence tomography (OCT) imaging of the retina, and electrical stimulation of the retina with a contact lens electrode. OCT images of 17 RP patients were acquired at the macula and at four quadrants of the peripheral retina in both eyes. Analysis was made of the residual inner retinal thickness and nerve fibre layer thickness in RP patients, and this was compared to normal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Although based only on this one case, we assume that a visible layering of the inner retina in a high‐resolution OCT is a good marker for its functionality. A correlation between electrical excitability of the inner retina and its thickness has been described by other research groups …”
Section: Methodssupporting
confidence: 55%
“…Although based only on this one case, we assume that a visible layering of the inner retina in a high‐resolution OCT is a good marker for its functionality. A correlation between electrical excitability of the inner retina and its thickness has been described by other research groups …”
Section: Methodssupporting
confidence: 55%
“…Huang et al [15] investigated the relative inner retinal preservation in vivo in the peripheral retina and the macula using tdOCT in patients with RP. There was a 7.39% increase in the inner retinal layer thickness in the periphery in comparison with normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…5 If the status of inner retina varies in each patient, selection of patients based on the preservation of inner retinal structures and functions would be helpful to achieve maximal effect from the treatments. 6 Histology studies concerning the status of the inner retina in RP are limited. [7][8][9][10] These histologic reports showed that up to 75% of ganglion cell layer cells are retained in the macular area in patients with RP; 7,8 however, the percentage decreases to 20-30% in extra-macular region 9 and 70-90% of total ganglion cells or their axons are lost eventually, 10 suggesting that inner retinal cells are partially preserved in RP, but degenerate as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%